Faithful readers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Eku & Kith s Common Initiative Group writes to us from Tombel in the South West Province of the Republic of Cameroon, to announce that they have established an agricultural library. 'The community has appreciated our initiative. We held a book...